Peran Tabungan Smart iB Makbul Dalam Meningkatkan DPK Di PT Bank SUMUT Capem Syariah HM Joni - Windi Mariska Suryani Siregar (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The aim of this research is to determine the role of IB Makbul smart savings in increasing DPK, which is located at PT Bank Sumut Capem Syariah HM Joni. The research uses quantitative methods. The population of this research is all employees at Bank Sumut CAPEM Syariah HM JONI Medan, totaling 13 people. The sampling technique in this research was to use a saturated sampling technique (total sampling). Based on the results of the Kendall's Tau B test above, the significant value is 0.114 > 0.05 which indicates that the relationship between the Smart Ib Makbul savings variable and the third party funds (DPK) variable is not significant or in other words there is no/sufficient relationship between the variables. The three interpretations in the Kendall's Tau-B correlation test above, a conclusion can be drawn that "the relationship between Smart Ib Makbul savings and third party funds (TPF) is not significant, sufficient, and in the same direction.